Die Kryptologie im Mathematikunterricht als Ideengeber für Facharbeitsthemen (mathematica didactica, 2002)
We show how to use cryptography in school to find subjects for papers written by pupils. By emphasizing the mathematical impact in cryptography we vote for dealing with number theory in high school.